Movement modifications related to psychological pressure in a table tennis forehand task - Sekiya, H.; Tanaka, Y. (Perceptual and Motor Skills, 2019)
Although many studies on choking under pressure used closed skills, such as golf putting, we examined the influence of pressure on movement during a dynamic skill by studying participants` kinematic and kinetic changes during a table tennis forehand task under pressure. Thirty novice table tennis players hit forehand shots toward a target for 135 practice trials and then performed 10 no-pressure and 10 pressure trials. We added psychological pressure by instructing participants they could earn monetary rewards for successful performance and by cancelling accumulated scores for a poor performance. We measured racket head and ball movements as kinematic variables and grip force as a kinetic variable. We also measured state anxiety and heart rate as checks on our manipulation of psychological pressure. In the pressure condition, both state anxiety and heart rate increased significantly (p < .025), though the pressure level was relatively small. Analysis of kinematic measures revealed that back swing and forward swing were reduced in length; speed of forward swing and ball speed decreased significantly (p < .008) under pressure. Also, under pressure, ball and racket contact point shifted forward significantly (p < .008) to reduce the distance between impact and target locations, and performance declined as the ball-landing locations shifted leftward (p < .007). Grip force showed no significant change. We conclude that, under pressure, movement was modified toward reduced displacement and lower speed in an apparent risk-aversive hitting strategy; these modifications resulted in a performance decrement.